GALVIS: Visualization Construction through Example-Powered Declarative Programming - Shen, Leixian; Shen, Enya; Tai, Zhiwei; Wang, Yun; Luo, Yuyu; Wang, Jianmin (Proceedings of the 31st ACM International Conference on Information & Knowledge Management (CIKM '22), 2022)
Declarative programmatic approaches are an essential modality for data visualization construction. Despite the powerful customization ability, declarative programming requires users to create charts from scratch, thus building a well-designed visualization is an effort-consuming process. In this paper, we propose leveraging examples to alleviate the problem. The use of examples plays a vital role in visualization design. Users can be allowed to browse through designs for inspiration and adapt them for their own visualizations. In this demo, we directly leverage the entire Vega/Vega-Lite example galleries as chart templates and introduce an authoring pipeline to conveniently instantiate templates with the user's data for extensible programmatic modifications. Finally, we build GALVIS, an example-powered declarative programming tool for visualization construction, enabling efficient declarative programming and retaining the full spectrum of Vega/Vega-Lite characteristics.